(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2020)
The waste sorting and recycling plant in the district of al- Mahmudiya (Yusufiya) is the only laboratory in Baghdad governorate. It is the only one in Iraq that collects and recycles waste. After sorting, we have packages of raw materials (aluminum cans, glass bottles, plastic bottles, Nylon bags) as well as natural fertilizers (food residues and others) and a sanitary landfill with specifications that meet international standards; However, the absence of a structure for the management of the plant (manager, assistant manager, accountant, etc.) in addition to the non-supply of waste on a daily and continuous basis and the lack of cooperation of the Municipality of Baghdad with the management of the plant led to delay in the work of the laboratory instead of providing support and possibilities for the purpose of expanding Sorting lines and waste reduction gradually as well as damage to sorted materials.